(untitled) (Journal of Nepal Geological Society, 1985)
ABSTRACT The apparent velocity distribution of the local seismic of lesser Himalaya of central and Eastern Nepal allows to derive a three layered local seismic velocity model with first layer velocity of 5.6 Km/Sec, second layer of 6.5 Km/sec. and Moho discontinuity with 8.1 Km/sec. The first arrivals of different local phases of seismic waves are consistent with 20-23 Km thickness of the first layer and with crustal thickness of 55Km. The seismic events are confined to the first layer. Local velocity model derived after the seismic event of 6 Oct 1981, origin time 19 hr 18 mn 17 sec, by modelling the first arrivals and PMP (Moho reflection) arrivals within the interval of distance 138-218 Km confirms the velocity model derived from apparent velocity distribution. However, apparent velocity distribution of local seismic events occurring south of the line joining approximately Pokhara to Udayapur in plan does not seem to fit the theoretical distribution corresponding to the above three layered model with events within first layer. The apparent velocity of these events may be explained either (a) by the confinement of the focus of the events to the second layer or, (b) by the variation of the seismic velocity model with Moho depth at 35- 40 Km. i.e. with a normal Indian peninsular crust thickness.